The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1200/jco.2009.25.9663
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, Open-Label, Randomized Study Comparing Concurrent Gemcitabine Plus Cisplatin and Radiation Followed by Adjuvant Gemcitabine and Cisplatin Versus Concurrent Cisplatin and Radiation in Patients With Stage IIB to IVA Carcinoma of the Cervix

Abstract: Gemcitabine plus cisplatin chemoradiotherapy followed by BCT and adjuvant gemcitabine/cisplatin chemotherapy improved survival outcomes with increased but clinically manageable toxicity when compared with standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
322
3
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(349 citation statements)
references
References 23 publications
15
322
3
9
Order By: Relevance
“…There were also more significantly hospitalization in the experimental group (30 versus 11 percent). Most of the excess toxicity occurred during chemoradiotherapy, the incidence of late toxicities in both groups were similar (Duenaz-Gonzalez et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…There were also more significantly hospitalization in the experimental group (30 versus 11 percent). Most of the excess toxicity occurred during chemoradiotherapy, the incidence of late toxicities in both groups were similar (Duenaz-Gonzalez et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
“…Radiation therapy is an effective choice for advanced cervical cancer treatment, but radiotherapy effect itself is not satisfactory, therefore, the U.S. National Cancer Institute (NCI) in February 1999 announced to the world, that the combination of radiotherapy and chemotherapy treatment at the same time in advanced cervical cancer have good effect and suggested for patients who received radiotherapy, chemotherapy should be given the same time (Peters et al, 2000). Recent studies confirmed that concurrent radiotherapy and chemotherapy in advanced cervical cancer is safe and feasible, have good effect Dueñas-González et al, 2011). However, cervical cancer is not always sensitive to Chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with locally advanced cervical cancer requiring treatment with concurrent chemoradiation (CCRT), approximately 30% develop new or persistent disease (PD) following treatment 2, 3. With recent studies showing significant improvements in progression‐free and overall survival with adjuvant chemotherapy albeit at a cost of grade 3 or greater toxicity approaching 90%,4 a capability for early identification of those cervical cancer patients at increased risk of new or PD would have potential to improve survival outcomes.…”
Section: Introductionmentioning
confidence: 99%